(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Loshtun O. Principles of training in the formation of professional competence of future teachers The article is devoted to solving the problem of training in the training of future teachers. The author analyzes the problems in the psychological and educational literature and defines the principles of the implementation of training sessions in high school.